PENEGAKAN HAK PRIORITAS PENGIRING AMBULANS OLEH MASYARAKAT SIPIL DITINJAU DARI PASAL 134 DAN 135 UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN - Joelian Rezky Utomo; Amad Sudiro (Fakultas Hukum Universitas Tarumanagara, 2022)
The enforcement of the priority rights of ambulance attendants by civil society must be dealt withfirmly, so that it reflects justice for all parties, whether they get priority or not. This study aims to findout how law enforcement is against violators of Article 134 of Law Number 22 of 2009 concerningroad users who have primary rights and to find out how the implementation of priority driving rightsaccording to articles 134 and 135 of Law Number 22 of 2009 concerning Traf ic and Transport Road.Ambulance escorts carried out by civil society has reduced violators who are still carrying outambulance escort activities, but it is still not ef ective because of the uneven knowledge of the policeregarding the provisions of Article 135 Traf ic and Road Transportation. violators are afraid andcreate prevention of violations of the priority rights of road users, this is evidenced by the presence ofcivil society ambulance escorts that still occur on public roads. The role of the Police in providingeducation is also needed so that there are no or multiple interpretations in understanding andunderstanding the laws that regulate Priority Right to Drive on Public Roads.